2004
DOI: 10.1517/14728222.8.2.95
|View full text |Cite
|
Sign up to set email alerts
|

Potential therapeutic targets for the treatment of detrusor overactivity

Abstract: Current treatments for the overactive detrusor are poorly tolerated and can exert significant adverse effects. Possible targets for the development of new treatments are considered. Potential targets in four locations are examined: detrusor smooth muscle, urothelium, peripheral nerves and the CNS. In the detrusor, the role of various muscarinic receptor subtypes is discussed and beta-adrenoceptor agonists, phosphodiesterase inhibitors and potassium channel openers, all of which inhibit detrusor contractility, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
4

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 78 publications
0
6
0
4
Order By: Relevance
“…Muscarinic receptor antagonists that impair UBSM contractility are the main option, but they have limited effectiveness and undesirable side effects (1,23). In recent years, ␤ 3 -adrenoceptor agonists, purinergic receptor antagonists, phosphodiesterase inhibitors, and K ϩ channel openers have all been considered to be potential candidates for the treatment of OAB syndrome (10). In this study, urinary pattern analysis using G833C-NCX1.3 tg/tg mice, in which the G883C mutation confers a resistance to KB-R7943-mediated inhibition (22), failed to reproduce the inhibitory effect of KB-R7943 on frequent urination detected in NCX1.3 tg/tg mice.…”
Section: Discussionmentioning
confidence: 99%
“…Muscarinic receptor antagonists that impair UBSM contractility are the main option, but they have limited effectiveness and undesirable side effects (1,23). In recent years, ␤ 3 -adrenoceptor agonists, purinergic receptor antagonists, phosphodiesterase inhibitors, and K ϩ channel openers have all been considered to be potential candidates for the treatment of OAB syndrome (10). In this study, urinary pattern analysis using G833C-NCX1.3 tg/tg mice, in which the G883C mutation confers a resistance to KB-R7943-mediated inhibition (22), failed to reproduce the inhibitory effect of KB-R7943 on frequent urination detected in NCX1.3 tg/tg mice.…”
Section: Discussionmentioning
confidence: 99%
“…There are data reporting that there are more M 2 receptors in the bladder than M 3 . Despite this, we do not know what physiological role these receptors serve or where they are located [17–22]. Possible mechanisms involving the M 2 ‐dependent regulation of detrusor contraction have been suggested.…”
Section: Discussionmentioning
confidence: 99%
“…Release of chemical mediators (NO, ATP, acetylcholine, substance P, PGs) (10,11,19,26,28,33) from urothelial cells suggests that these cells exhibit specialized sensory and signaling properties that could allow reciprocal communication with neighboring urothelial cells as well as nerves or other cells (i.e., immune, myofibroblasts, inflammatory) in the bladder wall. Recent studies have shown that both afferent as well as autonomic axons are located in close proximity to the urothelium (8,12).…”
Section: "Transducer" Function Of the Urothelium And Cell-cell Signalingmentioning
confidence: 99%